Comparative Study of Inclusive Education Programs for Women in Indonesia and Malaysia - Supianto Supianto; Sri Marmoah; Jenny Indrastoeti Siti Poerwanti; Siti Istiyati; Sukarno Sukarno; Hasan Mahfud (STAI Hubbulwathan Duri, 2024)
Education constitutes a fundamental right for all individuals, irrespective of gender. Despite this, gender-based educational disparities persist globally. This study conducts a comparative analysis of inclusive education programs for women in Indonesia and Malaysia, aiming to elucidate gender challenges in educational access and participation. Employing a qualitative methodology and comparative analysis, this research scrutinizes inclusive policies and initiatives within these nations, delineating their distinctions and commonalities. Data were collected through document reviews, observations, and interviews and subsequently subjected to comparative descriptive analysis. The findings reveal both countries' dedication to enhancing female educational participation. Nonetheless, obstacles such as restricted rural educational access, prevalent gender stereotypes in certain academic disciplines, discrepancies in STEM proficiency, and economic constraints continue to impede progress. To surmount these gender challenges in education, it is imperative to eradicate gender stereotypes, fortify gender-specific policies, broaden educational access, and provide tailored support for women with unique needs. Through collaborative efforts across multiple stakeholders, this study advocates for the establishment of an inclusive, equitable, and gender-fair educational milieu.